Son Preference, Eldest Son Preference, and Educational Attainment: Evidence From Chinese Families. (May 2020) - Wang, Weidong; Liu, Xiaohong; Dong, Yongqing; Bai, Yunli; Wang, Shukun; Zhang, Linxiu
Gender inequality has long been an important topic of concern. This article empirically measures whether there exists son preference and eldest son preference in China, from the perspective of an individual's educational attainment, by using the data set of China Family Panel Studies in 2010. We find that (a) sons receive more education than daughters, and that the gender education gap for rural residents is greater than that of residents from urban areas; (b) regardless of the eldest or noneldest sons, the education received by sons is significantly higher than that of daughters, and there is no significant difference between the eldest and noneldest son's education; (c) the gender education gap narrows over time, and expands as the number of sibling increases. Finally, we explore the multiple effect mechanisms.